Evaluating tobacco industry 'transformation': a proposed rubric and analysis. Issue 2 (3rd March 2022) - Edwards, Richard; Hoek, Janet; Karreman, Nancy; Gilmore, Anna
Abstract : Some tobacco companies claim they are 'transforming' by adopting harm reduction goals or even seeking to achieve a 'smokefree' world. What characterises transformation and whether companies can or are transforming is unclear. Nevertheless, such claims are gaining traction. We critically investigated tobacco industry transformation by exploring the definition and criteria for evaluating transformation, and assessed whether transformation is occurring and feasible. Companies' transformation claims centre on increasing sales of new tobacco and nicotine products like e-cigarettes ('new products') with little attention to reducing sales of more hazardous smoked and oral products ('conventional products'). We define a transforming tobacco company as one demonstrating substantial, rapid and verifiable progress towards eliminating the production and sale of conventional tobacco products within 5 years in all markets where it operates. We found no evidence any tobacco company is meeting the three essential criteria of rapidly progressing towards eliminating conventional products, ceasing to obstruct effective tobacco control measures and taking action to minimise smoking uptake and disparities. While some companies are developing new product portfolios, their actions are more consistent with profit maximisation than eliminating conventional product use. This approach is best described as 'pseudo-transformation', designed to delay implementation of effective tobacco control policies. In addition, our analysis suggests replacing conventional products with new nicotine products is unlikely to be a viable long-term business model. Public health practitioners should not rely on tobacco industry claims but should lead the transformation debate, establish credible definitions and criteria, and monitor and assess whether transformation is occurring.